Mapping Salivary Proteases in Sjögren’s Syndrome Patients Reveals Overexpression of Dipeptidyl Peptidase-4/CD26 - Garreto, Laís; Charneau, Sébastien; Mandacaru, Samuel Coelho; Nóbrega, Otávio T.; Motta, Flávia N.; de Araújo, Carla N.; Tonet, Audrey C.; Modesto, Flávia M. B.; Paula, Lilian M.; de Sousa, Marcelo Valle; Santana, Jaime M.; Acevedo, Ana Carolina; et al. (Frontiers in Immunology, 2021)
Sjögren's Syndrome (SS) is an autoimmune exocrinopathy characterized by the progressive damage of salivary and lacrimal glands associated with lymphocytic infiltration. Identifying new non-invasive biomarkers for SS diagnosis remains a challenge, and alterations in saliva composition reported in patients turn this fluid into a source of potential biomarkers. Among these, proteases are promising candidates since they are involved in several key physio-pathological processes. This study evaluated differentially expressed proteases in SS individuals' saliva using synthetic fluorogenic substrates, zymography, ELISA, and proteomic approaches. Here we reported, for the first time, increased activity of the serine protease dipeptidyl peptidase-4/CD26 (DPP4/CD26) in pSS saliva, the expression level of which was corroborated by ELISA assay. Gelatin zymograms showed that metalloproteinase proteolytic band profiles differed significantly in intensity between control and SS groups. Focusing on matrix metalloproteinase-9 (MMP9) expression, an increased tendency in pSS saliva (p=0.0527) was observed compared to the control group. Samples of control, pSS, and sSS were analyzed by mass spectrometry to reveal a general panorama of proteases in saliva. Forty-eight protein groups of proteases were identified, among which were the serine proteases Cathepsin G (CTSG), Neutrophil elastase (ELANE), Myeloblastin (PRTN3), MMP9 and several protease inhibitors. This work paves the way for proteases to be explored in the future as biomarkers, emphasizing DPP4 by its association in several autoimmune and inflammatory diseases. Besides its proteolytic role, DPP4/CD26 acts as a cell surface receptor, signal transduction mediator, adhesion and costimulatory protein involved in T lymphocytes activation.